Pengaruh Teknik Muhasabah pada Bimbingan Kelompok untuk Meningkatkan Keterampilan Self-awareness - Mu'thiya Zhilla Rahman; Dindin Solahudin; Dewi Sadiah (UIN Siber Syekh Nurjati Cirebon, 2025)
This research aims to examine the effectiveness of the application of deliberation techniques in group guidance towards the increase of self-awareness of class XI students at MA Persis Katapang. The background of this research is based on the importance of self-awareness as one of the non-cognitive skills that plays a role in shaping personality, including aspects of emotional self-awareness, accurate self assessment, and self confidence. The low self-awareness of students implies weak emotional control, inaccurate assessment of self-potential, and low self-confidence in making decisions. The research sample consisted of 63 students who were divided into experimental groups and control groups. The research instrument is in the form of a self-awareness questionnaire processed through t-test and N-Gain analysis. The research results showed that there was a significant increase in the experimental group after being given group guidance treatment with the deliberation technique. Learners show a better ability in recognizing emotions, assessing strengths and weaknesses objectively, and growing self-confidence. The t-test showed a significance value of < 0.05 which indicates a real difference between the experimental and control groups, while the N-Gain results were in the fairly effective category. Thus, the muhasabah technique is proven to have a positive effect on increasing students' self-awareness and can be used as an alternative strategy for Islamic-based counseling guidance services that are relevant to the development needs of students.